ARABIC- RENEWAL OF CURRICULA OF ISLAMIC STUDIES IN THE FUNDAMENTALS OF JURISPRUDENCE - Abdul Hai Madni; Makhdoom Muhammad RoshaN Siddiqui (دی اسکالر)
The  renewal, modification, up gradation and improvement is the need of time ,and there is a famous statement of our beloved Prophet ﷺthat supports this point: Allah sends to this nation at the head of every hundred years someone who performs a renewal of principals “so the legitimacy in some of required Religious matters is also needed for the proper guidance of Ummah,Imam Shafi’i,Ghazali,Ibne Tamiyyah etc are the best example for that. The renewal doesn't mean the replacement of old with something new but preserving the original and seeking the guidance to solve the occurring new problems is aimed. In fact the new doctrines of Jurisprudence represent a unique step of Islamic Sciences to consider the fundamentals and introduce the suitable methodology to devise Sharia Rulings for the required guidance. It is needed to renew and develop the necessary methodological tools to preserve the great Identity of Muslims by preserving their assets.There fore I like  to clarify that renewal of Jurisprudential rules is needed by writing a few points in this paper as  given below: Introduction to the fundamentals of jurisprudence, Definition of the assets of jurisprudence and its importance, concept of renewal, The difference between renewal and heresy, Method of renewal in the principles of jurisprudence, Results, Recommendations.